A study to model the post-mortem stability of 4-MMC, MDMA and BZP in putrefying remains. (August 2016) - Wenholz, Daniel S.; Luong, Susan; Philp, Morgan; Forbes, Shari L.; Stuart, Barbara H.; Drummer, Olaf H.; Fu, Shanlin
Highlights: Stabilities of 4-MMC, MDMA and BZP in putrefying samples were investigated. 4-MMC and BZP were found to degrade in putrefying matrices. MDMA was found to be stable to moderately stable in putrefying matrices. Higher temperatures accelerated the degradation of all three drugs. Putrefaction may cause a significant loss of 4-MMC in post-mortem specimens. Abstract: There is currently limited data available on the stabilities of the three stimulants 4-methylmethcathinone (4-MMC), 3, 4-methylenedioxymethamphetamine (MDMA) and N-benzylpiperazine (BZP) in a putrefying matrix. A Gas Chromatography Mass Spectrometry (GC-MS) method to determine the concentration of the three drugs in putrefying porcine liver over a three month period was developed and validated. Both 4-MMC and BZP were found to be unstable, becoming undetectable and having an average recovery of 52% respectively after one month at ambient room temperature (20 °C). MDMA was found to be moderately stable, with an average recovery of 74% after three months at room temperature. This study indicated that the putrefaction process could have a significant impact on concentrations of 4-MMC and BZP in post-mortem cases involving putrefied remains.